2021
DOI: 10.1002/adfm.202011198
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Lived Liquid Marbles for Green Applications

Abstract: Liquid marbles allow for quantities of various liquids to be encapsulated by hydrophobic particles, thus ensuring isolation from the external environment. The unique properties provided by this soft solid has allowed for use in a wide array of different applications. Liquid marbles do however have certain drawbacks, with lifetime and robustness often being limited. Within this review, particle characteristics that impact liquid marble stability are critically discussed, in addition to other factors, such as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 266 publications
0
20
0
Order By: Relevance
“…Liquid marbles (LMs), , nonstick droplets encapsulated with hydrophobic micro/nanoparticles, have gained attention due to their potential applications such as gas sensors, , water pollution detection, micropumps, microbioreactors, and medium for cultivating micro-organisms. , In contrast to the pristine liquid droplets, the LMs provide less friction, reduced evaporation, and easier manipulation like a soft solid. The properties of the encapsulated particles and the volume of the marbles play a pivotal role in their stability and functionalities. The role of particles has been extensively studied, both in terms of fundamental aspects as well as applications. It is worth it to mention that the LMs enwrapped with stimuli-responsive particles can be actuated with various external stimuli, such as light, temperature, electric field, and magnetic field. ,, In terms of the volume of the liquid marbles, all of the reported works utilized marbles having a volume above 2 μL.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid marbles (LMs), , nonstick droplets encapsulated with hydrophobic micro/nanoparticles, have gained attention due to their potential applications such as gas sensors, , water pollution detection, micropumps, microbioreactors, and medium for cultivating micro-organisms. , In contrast to the pristine liquid droplets, the LMs provide less friction, reduced evaporation, and easier manipulation like a soft solid. The properties of the encapsulated particles and the volume of the marbles play a pivotal role in their stability and functionalities. The role of particles has been extensively studied, both in terms of fundamental aspects as well as applications. It is worth it to mention that the LMs enwrapped with stimuli-responsive particles can be actuated with various external stimuli, such as light, temperature, electric field, and magnetic field. ,, In terms of the volume of the liquid marbles, all of the reported works utilized marbles having a volume above 2 μL.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic particle processing is of growing interest in both research and industrial arenas. A particularly interesting example is the formation of liquid marbles; liquid droplets armored by adsorbed nonwetting particles. Once encapsulated, these liquid marbles demonstrate remarkable elasticity , and locomotive properties while retaining gas permeability. ,, These structures have been of substantial research interest for the last 20 years since they were first reported by Aussillous and Quéré. , Some proposed applications of these structures have included their use as microreactors for rapid blood typing and chemical detection, as well as a microvessel for targeted payload delivery. However, their implementation in many proposed applications is hindered due to the lack of scalable and controllable mass production techniques. , The electrostatic method of liquid marble formation using an electric field is a potential remedy for this engineering hurdle. ,,, This technique is underpinned by direct delivery of particulate matter to a pendent droplet without direct contact between the droplet and the particle reservoir using an electrostatic field. , This allows for the formation of liquid marbles of controllable size, coating, and composition using a range of materials. Studies of this particular technique have focused on a variety of materials including polymers such as polystyrene and conductive hydrophobic particles. , Investigation of nonconducting or dielectric hydrophobic particles has been limited to date. Previous work using cinnamon particles revealed an unusually large (μm), and uniform interparticle spacing on the pendent droplet surface upon initial particle transfer .…”
Section: Introductionmentioning
confidence: 99%
“…LMs are liquid droplets coated by solid particles that exist in air. Since the LMs were brought into the limelight in 2001, studies of the principle, formation, characterization, and applications of the LMs have been conducted for 20 years in an interdisciplinary manner. The w/a LM could be readily fabricated by rolling a water droplet over the dried PDEA–PS particle powder bed (Figure b) .…”
Section: Resultsmentioning
confidence: 99%
“…There has been increasing interest in colloidal particles adsorbed at fluid interfaces (e.g., oil–water and air–water interfaces), which lead to stabilization of soft dispersed systems consisting of immiscible fluids, such as emulsions, foams and/or bubbles, liquid marbles (LMs), and dry liquids. , Adsorption of the particles at the fluid interfaces is driven by the interfacial free energy gain in losing the fluid–fluid interfacial area obliterated by the particles. The wettability of the particles at the interface, which is quantified by three-phase contact angle θ measured through the aqueous phase, is known to play an important role in determining the type of soft dispersed systems .…”
Section: Introductionmentioning
confidence: 99%